The Effect Of Microcredit On Women Empowerment In Welfare And Decisions Making In Malaysia - Al-Shami, Samer Ali Hussein; Razali, R. M.; Abdul Rashid, Nurulizwa (Springer Netherlands, 2018)
Microcredit is perceived as an effective tool to empower women, especially those who are deprived of accessing financial services. However, the literature has arrived with contradictory evidence and demonstrates that the effect of microcredit may partially or not empower women. This study intends to examine whether the access to Amanah Ikhtiar Malaysia (AIM) affects several aspects of empowerment in urban Malaysia. A cross-sectional survey was distributed to 474 old and new clients to examine the effect of microcredit on women empowerment in decision-making process and resource controlling. Based on the propensity score matching, our result shows that the access to AIM microcredit affects positively women’s monthly income. In addition, microcredit empowers women borrowers in a set of household decisions making including mobility, daily expenditure, children school, health expenditure and loan order decision.